Membrane and Extracellular Matrix Glycopolymers of Colwellia psychrerythraea 34H: Structural Changes at Different Growth Temperatures - Casillo, Angela; D’Angelo, Caterina; Parrilli, Ermenegilda; Tutino, Maria Luisa; Corsaro, Maria Michela (Frontiers in Microbiology, 2022)
Colwellia psychrerythraea 34H is a marine Gram-negative psychrophile, it was isolated from Arctic marine sediments, but it is considered cosmopolitan in cold environments. This microorganism is considered a model to study adaptive strategies to sub-zero temperatures and its lifestyle has been the object of numerous studies. In the last years, we focused our studies on the glycoconjugates produced by C. psychrerythraea 34H at 4 °C, resulting in the isolation and characterization of very interesting molecules. It produces an unusual lipooligosaccharide molecule and both capsular and medium released polysaccharides. In this study, we described the response of these glycoconjugates in terms of production and chemical structure produced by C. psychrerythraea 34H grown in planktonic conditions at -2 °C, 4 °C, and 8 °C. The glycopolymers have been detected by chemical methods and spectroscopic analyses. Moreover, the glycopolymer content of the biofilm matrix of C. psychrerythraea 34H has been evaluated, through confocal microscopy and glycosyl analysis. The results highlighted that C. psychrerythraea 34H adjusts both the production and the typology of its glyconjugates in response to temperature fluctuations.